Creativity in Science - Goodenough, Ursula W. (Zygon, 1993)
Abstract. Creativity is a concept far more often associated with art than with science. The creative dimension of scientific inquiry and practice is described and compared with its artistic counterpart; similarities and differences are analyzed.